Patients’ Participation in Surgical Treatment Decision Making in General Government Hospital of Bharatpur - Dharel, Soni; Pokhrel, Jyoti; Upadhyay, Hari Prasad; Sedain, Prativa (International Journal of Silkroad Institute of Research and Training, 2023)
Background: Patient participation means involvement of the patient in decision making or expressing their opinions about different treatment methods, which includes sharing information, feelings and signs and accepting and rejecting health team instructions. The study aims to find out the level of patient participation in surgical treatment decision making of admitted patient in general government hospital of Chitwan.Methods: A descriptive cross –sectional research was carried out to assess the level of participation in surgical treatment decision making. Non-probability, purposive sampling technique was used. A set of valid instruments containing 16 item was used to assess the level of participation. Ethical clearance was taken from Institutional review Committee of Shree Medical and Technical College (SMTC-IRC 20221206-43). Data were collected and analyzed in statistical package for the social science version. Results: The result of the study shows that maximum respondents 51.8% belonged to age group less or equals to 40 years. Among 226 respondents 58.4% were female and 41.6% were male. Among them, more than half (62.8%) of the respondent had high level of participation and (37.2%) of the respondents had low level of participation.Conclusions: The findings of the study indicate the participation of patient in surgical treatment decision making. These findings may help hospital and concerned authorities to make appropriate policy and take corrective action to increase the level of patient participation in treatment decision making.